Studi Literatur: Potensi Material Fe₃O₄/Zeolit sebagai Adsorben Efektif untuk Pengolahan Limbah Cair Industri - Saputro, Erwan Adi; Mohamad Rizki Ramadhani; Alya Rahimah; Ardika Nurmawati (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Industrialization and population growth in Indonesia have led to a decline in environmental quality. The increasing activities of industries such as textiles, metal plating, mining, and pharmaceuticals have also generated large amounts of hazardous organic and inorganic wastewater. Adsorption has become a preferred method for treating such waste, particularly through the use of zeolite materials modified with magnetite (Fe₃O₄) to enhance efficiency and ease of separation. The Fe₃O₄/zeolite material exhibits high adsorption capacity toward various pollutants, making it a potential adsorbent for industrial wastewater treatment. This review aims to examine the potential of Fe₃O₄/zeolite as an adsorbent through a literature study by collecting and analyzing secondary data from various scientific publications. The selected literature was analyzed to compare synthesis methods, operating conditions, and adsorption efficiencies in order to obtain a comprehensive understanding of the performance and adsorption mechanism of Fe₃O₄/zeolite. Based on the review, Fe₃O₄/zeolite demonstrates good adsorption efficiency, with recorded values ranging from 42% to 99%.